Developing The Integrated Environmental Accounting Measurement in Islamic Bank - Lilly Anggrayni; Sofyan Oktavian Tubagus; Mentary Ariesta Iyonu (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2023)
This study is aim to develop the new measurement of environmental accounting that fit with the nature of Islamic Banks. This study employed quantitative approach to measure the intensity of the samples in implemented the environmental accounting. The Islamic Banks (IBs) usually employed the conventional yardstick in measuring the environmental accounting. Otherwise, this yardstick is not fit with the IBs nature. Therefore this study suggests the usage of the integrated environmental accounting measurement on IBs, that more accurate than the index measurement. The originality of this study lies on the measurement method of environmental accounting which was developed from several relevant studies. This study had major implication for practitioners of IBs and also environmental accounting thinker